Ideology, language and the politics of time - Ewing, A (2017)
This thesis examines the temporal dimension of political thought. From the standpoint of ideology studies, it incorporates methods and findings in conceptual history and in the work of Reinhart Koselleck, the primary theorist in the field, to the study of political thinking. Building on Koselleck’s theorisation on the semantics of historical time, the thesis investigates the ways that political ideologies, which primarily influence political activity through the control of language, linguistically mediate historical time for political purposes. There are three parts to the thesis. The first is an assessment of the existing scholarship on the study of political thinking and time in the field of ideology studies, followed by an analysis of Koselleck’s hitherto unincorporated writings on historical time. The second offers an initial typology of three core ‘modes’ of the ideological politicking of time—on the politics of contingency, the politics of horizons and the politics of movement—each incorporating particular themes from Koselleck’s writings. The third puts Koselleck in conversation with two British political thinkers with whom he did not engage—J. S. Mill and Michael Oakeshott—in an effort to unpack contestations of historical time in their respective works. On both these levels—the typological and by way of conversation—the thesis endeavours to give a better understanding of the routine ways in which politics contests and shapes historicity. Yet doing so also concerns the influence of time on politics. It suggests that political practice is not simply an activity to study ‘in time’, but is also, on the level of experience, a contestation of time itself.